Impacts of land use land cover change on Leopard (Panthera pardus) habitat suitability and its effects on human wildlife conflict in Hirkiso forest, Sibu Sire District, Western Ethiopia - Mengistu Muleta Gurmessa; Mitiku Badasa Moisa; Gutema Jira Tesso; Mosissa Geleta Erena (All Earth, 2024)
Land use and land cover (LULC) change reduced Leopard’s habitat suitability and caused a serious human-wildlife conflict. The study aimed to analyse the impacts of LULC change on Panthera pardus habitat suitability and its effects on human wildlife conflicts in the study area. The parameters like LULC, slope, elevation, settlement, road and river, and socio-economic survey were considered. GIS-based MCE with AHP method and Software like ArcGIS 10.3, ERDAS Imagine 2015, IDRISI Selva, and Google Earth Pro were used for data analysis. The results revealed that grassland, forestland, and wetland covers were declined with 25.4 km2, 14.8 km2, and 4.3 km2 and led to a reduction of highly suitable (6 km2) and moderately suitable (25.6 km2) habitat for Panthera pardus respectively, over the study period. Respondents viewed that Papio anubis (40%) and Chlorocebus pygerythrus (19.05%) were highly conflicting wild mammals to humans every time. The findings suggest that stakeholders should implement strategies to mitigate unsustainable LULC changes. This approach is essential for preserving suitable wildlife habitats and reducing human-wildlife conflicts in the study area. Effective land management practices should be prioritised to ensure ecological balance and enhance biodiversity conservation efforts.